2000
DOI: 10.1002/(sici)1097-4652(200004)183:1<129::aid-jcp15>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal cell kinase (ICK) localizes to the crypt region and requires a dual phosphorylation site found in map kinases

Abstract: Identification of key regulatory kinases in the intestinal epithelium are useful to understand the molecular mechanisms that underlie proliferation and differentiation in cells found in this compartment. We used the polymerase chain reaction (PCR) to amplify the catalytic kinase domain of serine-threonine kinases by employing degenerate primers and then screened an intestinal crypt cDNA library to clone and sequence the open reading frame of a novel serine-threonine kinase. This was then further characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 20 publications
2
57
0
Order By: Relevance
“…Thus, the b-catenin signal in conjunction with p21-mediated G1-arrest is both necessary and sufficient for induction of intestinal-specific molecules in gastric epithelial cells. Consistently, DNA microarray analysis revealed that CagA also upregulates intestinal-specific genes such as intestinal cell kinase and an intestine crypt transcription factor SOX9 (Table 1) (Togawa et al, 2000;Blache et al, 2004). Among genes transcriptionally upregulated by CagA, those that unchanged by serum starvation are picked up.…”
Section: Induction Of Intestinal Transdifferentiation In Gastric Epitmentioning
confidence: 65%
“…Thus, the b-catenin signal in conjunction with p21-mediated G1-arrest is both necessary and sufficient for induction of intestinal-specific molecules in gastric epithelial cells. Consistently, DNA microarray analysis revealed that CagA also upregulates intestinal-specific genes such as intestinal cell kinase and an intestine crypt transcription factor SOX9 (Table 1) (Togawa et al, 2000;Blache et al, 2004). Among genes transcriptionally upregulated by CagA, those that unchanged by serum starvation are picked up.…”
Section: Induction Of Intestinal Transdifferentiation In Gastric Epitmentioning
confidence: 65%
“…Interestingly, we could not find an obvious homologue in Plasmodium, which has cilia, but the cilia are assembled in the cytoplasm in a process that does not require IFT (42). Mammals have three putative DYF-5 homologues that form a small subfamily of MAP kinases, the MAK kinases (22)(23)(24)(25). The functions of these MAK, MOK, and ICK/MRK proteins remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…dyf-5 encodes a protein of 471 aa, which shows extensive homology to three mammalian proteins that form a small subfamily of MAP kinases. This subfamily consists of MAK (male germ cell-associated kinase) (22), ICK or MRK (intestinal cell kinase and MAKrelated kinase, respectively) (23,24), and MOK (MAPK/MAK/ MRK overlapping kinase) (25), with highly conserved N-terminal catalytic domains and more divergent C-terminal noncatalytic domains. Although the functions of these kinases in mammals are not known, studies in other organisms suggest a function in the cilia.…”
mentioning
confidence: 86%
“…ICK, which is highly expressed in intestinal crypt epithelium, shares sequence similarity with mitogen-activated protein kinase (MAPK) family proteins (2). The catalytic activity of ICK is regulated by dual phosphorylation of a MAPK-like TDY motif in the activation T loop as well as the phosphorylation of Thr residues in the TDY motif by cell-cycle-related kinase (CCRK) (3).…”
mentioning
confidence: 99%